Deciphering phenotypic variance in different models of DNA-PKcs deficiency. - Neal, Jessica A. (DNA Repair (Amst), 2018)
DNA-PKcs deficiency has been studied in numerous animal models and cell culture systems. In previous studies of kinase inactivating mutations in cell culture systems, ablation of DNA-PK’s catalytic activity results in a cell phenotype that is virtually indistinguishable from that ascribed to complete loss of the enzyme. However, a recent compelling study demonstrates a remarkably more severe phenotype in mice harboring a targeted disruption of DNA-PK’s ATP binding site as compared to DNA-PKcs deficient mice. Here we investigate the mechanism for these divergent results. We find that kinase inactivating DNA-PKcs mutants markedly radiosensitize immortalized DNA-PKcs deficient cells, but have no substantial effects on transformed DNA-PKcs deficient cells. Since the non-homologous end joining mechanism likely functions similarly in all of these cell strains, it seems unlikely that kinase inactive DNA-PK could impair the end joining mechanism in some cell types, but not in others. In fact, we observed no significant differences in either episomal or chromosomal end joining assays in cells expressing kinase inactivated DNA-PKcs versus no DNA-PKcs. Several potential explanations could explain these data including a non-catalytic role for DNA-PKcs in promoting cell death, or alteration of gene expression by loss of DNA-PKcs as opposed to inhibition of its catalytic activity. Finally, controversy exists as to whether DNA-PKcs autophosphorylates or is the target of other PIKKs; we present data demonstrating that DNA-PK primarily autophosphorylates.